2021
DOI: 10.1371/journal.pone.0246359
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic insertion of the cyanobacterial membrane protein ictB increases grain yield in Zea mays through increased photosynthesis and carbohydrate production

Abstract: The C4 crop maize (Zea mays) is the most widely grown cereal crop worldwide and is an essential feedstock for food and bioenergy. Improving maize yield is important to achieve food security and agricultural sustainability in the 21st century. One potential means to improve crop productivity is to enhance photosynthesis. ictB, a membrane protein that is highly conserved across cyanobacteria, has been shown to improve photosynthesis, and often biomass, when introduced into diverse C3 plant species. Here, ictB fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
(106 reference statements)
1
7
0
Order By: Relevance
“…In agreement with this, transgenic RbcS::ictB maize lines had a 3.49% increase in yield compared to controls in field trials, with the increased performance attributed to enhanced carbohydrate production ( Koester et al, 2021 ). Yield increase was associated with an increase in photosystem II operating efficiency, suggesting that enhanced photosynthesis was responsible for the improvements ( Koester et al, 2021 ). These results support the hypothesis that IctB is not a CCM bicarbonate transporter: a complete understanding of how CCMs operate therefore remains lacking.…”
Section: A Year At the Forefront Of Engineering Photosynthesissupporting
confidence: 62%
See 2 more Smart Citations
“…In agreement with this, transgenic RbcS::ictB maize lines had a 3.49% increase in yield compared to controls in field trials, with the increased performance attributed to enhanced carbohydrate production ( Koester et al, 2021 ). Yield increase was associated with an increase in photosystem II operating efficiency, suggesting that enhanced photosynthesis was responsible for the improvements ( Koester et al, 2021 ). These results support the hypothesis that IctB is not a CCM bicarbonate transporter: a complete understanding of how CCMs operate therefore remains lacking.…”
Section: A Year At the Forefront Of Engineering Photosynthesissupporting
confidence: 62%
“…If IctB is not a bicarbonate transporter, previous suggestions that ictB expression in C 3 species enhances photosynthesis by facilitating a CCM ( Lieman-Hurwitz et al, 2003 ; Simkin et al, 2015 ; Gong et al, 2015 ; Hay et al, 2017 ) must be overlooking an alternative function. ictB expression in a C 4 species should therefore recapitulate the enhanced photosynthesis phenotype of ictB expression in C 3 plants ( Koester et al, 2021 ). In agreement with this, transgenic RbcS::ictB maize lines had a 3.49% increase in yield compared to controls in field trials, with the increased performance attributed to enhanced carbohydrate production ( Koester et al, 2021 ).…”
Section: A Year At the Forefront Of Engineering Photosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The results regarding the effect of ictB on crop biomass production have so far been inconclusive. For example, in some cases, ictB -overexpressing plants have produced significantly greater biomass ( Lieman-Hurwitz et al , 2003 ; Hay et al , 2017 ; Koester et al , 2021 ), while in other studies overexpression of ictB did not significantly alter biomass production ( Gong et al , 2015 ). This suggests that the mechanism that underlies ictB may be greatly affected by environmental factors, and that an increase in crop productivity may only happen under certain conditions, although these conditions have yet to be identified.…”
Section: Discussionmentioning
confidence: 95%
“…Paddy-grown rice expressing ictB had significantly (10.5%) higher mesophyll conductance ( g m ) and 13.5% higher A compared with the WT ( Gong et al , 2015 ). Field-grown maize also benefited with increases in A and carbohydrate production, with increases in yield of up to 9.4% ( Koester et al , 2021 ). Replicated field trials of ictB -expressing soybean showed significant increases of 25% in g m , 14% in A , and 15% in seed yield relative to the WT ( Hay et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%